The commemoration of the dead in contemporary Asiatic Yupik ritual space - Oparin, Dmitriy (Études/Inuit/Studies, 2012)
Contemporary Asiatic Yupik living in Chukotka (Russia) practise various types of ritual feeding of the spirits. People feed the spirits for specific purposes and at different places. The core ritual of feeding the deceased is an autumn commemoration of the dead (aghqesaghtuq), which is described in this article with examples from Novoe Chaplino and Sireniki. This seemingly simple ceremony is full of nuances, and each family practises it in its own manner. The variability of this ritual and the many models of behaviour within present-day ritual space reflect social diversity. Two aspects, the diverse practices of feeding the spirits and the specific ritual of commemoration of the dead, are key to understanding different social and cultural processes in Yupik villages.